Automation of Insect Mass Rearing and Processing Technologies of Mealworms (Tenebrio molitor) - Kröncke, Nina; Baur, Andreas; Böschen, Verena; Demtröder, Sebastian; Benning, Rainer; Delgado, Antonio (African Edible Insects As Alternative Source of Food, Oil, Protein and Bioactive Components, 2020)
Automating the production of insects for rearing, harvesting and processing is an important step in making insect mass production more attractive, cost effective and competitive. In this study, we present a functional model for the automated separation and monitoring of the breeding process of mealworms. Data have shown that it is possible to separate mealworm larvae from the substrate and faeces effectively with a zig-zag air separator and make handling and separating processes easier by automation. In addition, an integrated camera system with a neural network can assist in assessing the constitution of mealworms by using the segments of the larvae for evaluation. Regarding the processing of mealworm larvae, it has been shown that duration of drying and temperature have a significant influence on the nutritional value and quality of the larvae. In addition, the oil of the dried larvae was extracted with a screw press and the protein-rich press cake was processed with a rolling mill to insect meal, which is comparable to fishmeal and suitable for use in pet food and livestock fee
Keywords: Tenebrio molitor; Drying; Automation; Air classification; Image processing